Eye-gaze processing in the broader bipolar phenotype revealed by electrical neuroimaging. (30th September 2019) - Berchio, Cristina; Küng, Anne-Lise; Kumar, Samika; Cordera, Paolo; Dayer, Alexandre G.; Aubry, Jean-Michel; Michel, Christoph M.; Piguet, Camille
Highlights: The P200 differentiated BD patients and offspring from controls. Source imaging provided insight into potentially dysfunctional P200 networks. Deviant eye-gaze processing is associated to risk for BD. Abstract: Previous studies have documented atypical brain responses to faces in individuals with bipolar disorder (BD) and in their relatives. In view of previous findings of atypical face processing in youths at risk for BD, the aim of this study was to examine whether BD patients and offspring would show differential activation in networks of the social brain when processing eye-gaze. Data from 18 euthymic BD patients and 18 offspring, as well as 36 age-matched healthy controls, were collected using a delayed face-matching paradigm, event related potentials and electrical neuroimaging methods. The P200 component, which is implicated in facial cues decoding, differentiated the BD groups from their age-matched controls. P200 source reconstruction indicates impairments conveyed by eye-contact in a network involved in experiencing others' social intentions in BD patients (supplementary motor cortex, precentral gyrus, inferior parietal lobe), and the engagement of compensatory prefrontal mechanisms for modulating these functions in BD offspring. When viewing faces that had an averted gaze, BD patients and offspring showed a hypo-activation, compared to controls, particularly in regions involved in experiencing others' feelings (post-central gyrus in BD patients / ventral premotor cortex in offspring). Therefore, the neural mechanism for decoding shifts in eye-gaze may be a familial characteristic of BD.